Efficacy and safety of calcitonin gene‐related peptide antagonists in migraine treatment: A meta‐analysis. Issue 4 (8th March 2022) - Huang, Tingting; Xu, Yang; Chen, Yajie; Bian, Jing; Chu, Zhaohu; Zhao, Shoucai; Ma, Lingsong
Abstract: Introduction: We systematically reviewed the efficacy and safety of Calcitonin Gene‐Related Peptide (CGRP) antagonists for migraine treatment. Methods: Various databases including PubMed, Embase, The Cochrane Library, Chinese National Knowledge Infrastructure (CNKI), WanFang Data were electronically searched for randomized controlled trials (RCTs) on CGRP antagonists for migraine treatment since inception to March 2021. The trials were screened for inclusion, after which the methodological quality of the included trials was assessed. Then meta‐analysis was performed using the Revman 5.3 software. Results: A total of 26 RCTs involving 21, 736 patients were included. The CGRP antagonists group included 13, 635 patients while the control group included 8101 patients. Meta‐analysis showed that compared to the control group, CGRP antagonists were associated with various significant effects, including the following outcome indicators: (1) number of patients with ≥50% reduction from baseline in mean monthly migraine days (RR = 1.50, 95% CI [1.39, 1.62], p < .00001); (2) number of patients with pain free at 2 h postdose (RR = 1.98, 95% CI [1.77, 2.20], p < .00001), and (3) number of patients with 2–24 h sustained pain free postdose (RR = 2.18, 95% CI [1.93, 2.46], p < .00001). However, the number of patients with any adverse events was significantly high in the antagonists group, relative to the control group (RR = 1.08, 95% CI [1.04, 1.12], p < .0001). Conclusions: CGRP antagonists are significantly effective for migraine treatment; however, they are associated with various adverse events. Due to limitations with regards to quantity and quality of the included studies, the above conclusions should be verified by more high quality studies. Abstract : CGRP antagonists can be new drugs to treat migraine patients according to their effectiveness to relieve headaches, while the safety of the drugs still need more high‐quality research to prove.